La Multitarea y la Tecnología en estudiantes universitarios del área de salud: Multitasking and technology in university students in the Health area (La U Investiga, 2020)
Multitasking is the habit of performing several tasks of different kinds in parallel, this is more common and frequent in young generations, who are known as Digital Natives, among others; those who live framed in a world of cyberspace, social networks, electronic devices. Several questions arise from this reality: about the efficiency in the learning of young people with this habit; As teachers, have the appropriate strategiesto arrive with the pertinent knowledge to this group of young people, and the most important, on which our research is focused, obtain a first analysis of multitasking habits in students of the medical area. Thus, the contribution of this work consists in transferring this question to the university environment to diagnose these habits. For this purpose, information has been obtained through surveys of medical students, witha sample of 289 informants. The results show that there is a lower percentage who have the habit of multitasking, in addition, that the relationship between academic performance and the use of technologies would not determine this habit, but that there is a linear relationship with the age and gender of young people.
Keywords: multitasking; health area students; technology; digital natives; millennials